2018
DOI: 10.1111/ane.12973
|View full text |Cite
|
Sign up to set email alerts
|

Age and surgical outcome of low-grade glioma in Sweden

Abstract: In general, older patients with LGG have several unfavorable prognostic factors compared with younger patients but seem to tolerate surgery in a comparable fashion. However, more neurological deficits were observed following resections in elderly. Our data further support a cutoff at 50 years rather than 40 years for selection of high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
10
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 51 publications
(86 reference statements)
6
10
2
Order By: Relevance
“…The clinical features of glioma are also important factors in uencing the prognosis of patients. We found that the risk score of older patients was higher than the youth, which means a worse prognosis in older patients, and the phenomenon was consistent with the existing research conclusions (32). Compared with the low-risk group, the high-risk group was mainly composed of GBM and lower-grade glioma (G2/G3) with poor prognosis.…”
Section: Discussionsupporting
confidence: 89%
“…The clinical features of glioma are also important factors in uencing the prognosis of patients. We found that the risk score of older patients was higher than the youth, which means a worse prognosis in older patients, and the phenomenon was consistent with the existing research conclusions (32). Compared with the low-risk group, the high-risk group was mainly composed of GBM and lower-grade glioma (G2/G3) with poor prognosis.…”
Section: Discussionsupporting
confidence: 89%
“…In one study, age has been shown to be a risk factor for postoperative ND. 12 However, in our study, age was not seen as a significant factor affecting the NDs.…”
Section: Postoperative New Neurological Deficitscontrasting
confidence: 72%
“…Patients with sGBM and new neurological impairments had worse OS than those without neurological de cits and primary low-grade glioma and GBM. [27] Our ndings indicated that new neurological impairments were a detrimental factor for the OS of patients with sGBM. In addition, for patients in group F, GTR and a consistent or increased postoperative KPS score were favorable independent factors for OS.…”
Section: The Value Of New Neurological Impairments In Patients With Sgbmmentioning
confidence: 66%